Advanced method for increased singlet oxygen quantum yield for diaxially chalcone derivative silicon (IV) phthalocyanines - Karanlik, Guerkan; Karanlik, Ceren Can; Goreci, cigdem Yoruer; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This paper includes both the synthesis and photophysical, photochemical and sono-photochemical properties of three novel diaxially heteroaromatic hybrid chalcone substituted silicon (IV) phthalocyanine complexes (SC-Pc, NC-Pc and BrC-Pc). In sono-photochemical methods, both ultrasound and light were used for excitation of sensitizers. These synergistic effects helped to enhance singlet oxygen generation. Singlet oxygen quantum yield (Phi Delta), was calculated as 0.24, 0.68 and 0.72 for SC-Pc, NC-Pc and BrC-Pc, respectively, using only the light irradiation in photochemical method (PDT), while these values were increased to 0.40 for SC-Pc, 1.02 for NC-Pc and 0.92 for BrC-Pc using both light and ultrasound irradiation together in sono-photochemical method (SPDT). This study will contribute to the limited literature by demonstrating the potential of chalcone-substituted phthalocyanine derivative sensitizers to enhance singlet oxygen generation through the sono-photochemical method.
Keywords: Chalcone; Heteroaromatic moiety; Singlet oxygen; Sono-photochemical method; PHOTODYNAMIC THERAPY; RECENT PROGRESS; IN-VITRO; PHOTOSENSITIZERS; CANCER; Chemistry; Crystallography